Genetic characterization and antimicrobial resistance patterns of Burkholderia pseudomallei isolates from animals and environment in Peninsular Malaysia - Muhammad, Abubakar Sadiq (2017)
Burkholderia pseudomallei is the aetiological agent of an emerging and potentially fatal human and animal disease melioidosis. Much of the knowledge about this organism in Malaysia and elsewhere revolved around human clinical isolates and much less is known about animal and environmental isolates. The present study was conducted with the aim generating more information on the phylogenetic variability of the animal and environmental B. pseudomallei isolates and its relatedness to antibiotic resistance pattern and genes. The specific objectives are to determine the molecular characteristics of B. pseudomallei isolates from animals and the environment (soil and water) in Peninsula Malaysia, compare the phylogeny of these isolates to those from elsewhere in the world, determine the antimicrobial resistance pattern among animal and environmental isolates, determine the occurrence of antimicrobial resistance genes and compare to the resistance pattern observed and determine the association between the sequence types to the physical and chemical characteristics of environments (soil and water) where the isolates originated.A total of 113 Malaysian B. pseudomallei isolates from animals and farm environment (soil and water) were characterised by multilocus sequence typing (MLST). Eighteen alleles were recovered in this study, among which are novel allele 97 and 69 of gene locus ace and lepA respectively. The allelic combinations resolved the isolates into 12 distinct sequence types (STs) with five among which are novel STs; ST1130, ST1131, ST1338, ST1339 and ST1367. This study found no association between sources of isolates and ST whereby the STs recovered from animal cases co-cluster with those found in the environment and have also been previously reported in humans. The isolates were found to be highly clonal. Moreover, B. pseudomallei strains were recovered to have descended from a common ancestor clonal complex 48 (CC48) found regionally in Southeast Asia. Disc diffusion or Kirby Bauer and E-test minimum inhibitory concentration (MIC) antibiotics susceptibility tests were conducted on 111 B. pseudomallei isolates. Twelve (12), common commercially prepared antimicrobial discs: ceftazidime, ceftriaxone, meropenem, ticarcillin, aztreonam, trimethoprim-sulfamethoxazole (cotrimoxazole), ciprofloxacin, imipenem, chloramphenicol, gentamicin, tetracycline and doxycycline were used in the disc diffusion method. All (100%) of the B. pseudomallei showed susceptibility to chloramphenicol, imipenem and doxycycline while all the isolates in this study were resistant to gentamicin and ticarcillin, and 99% were resistant to aztreonam. There was no significant association between the source of isolates (whether from animals or the environment) to the occurrence of resistance to any of the 12 antibiotics by disc diffusion method (p> 0.05), however there was a significant association between the occurrence of resistance to meropenem (p<0.05) and cotrimoxazole (p<0.001) to the STs of B. pseudomallei isolates. Five antibiotics namely meropenem, imipenem, ceftazidime, trimethoprim-sulfamethoxazole and amoxicillin-clavulanic acid, recommended in both acute and eradication phases of melioidosis treatment were tested using E-test MIC method. The majority of isolates were susceptible to all the antibiotics tested, however the existence of few resistant strains to meropenem, cotrimoxazole, ceftazidime and co-amoxiclav was observed among these isolates. A statistically significant association was found between resistance to meropenem and the animal isolates (p<0.05). The likelihood of resistance to meropenem was significantly higher among the novel sequence type (ST) 1130 isolates found in animal cases as compared to others.Burkholderia pseudomallei was reported to exhibit high resistant to many antibiotics by employing several resistance mechanisms. Five components B. pseudomallei antibiotic resistance genes of resistance nodulation division (RND), namely MxFs_BPSS1119, bpeA, bpeB, amrB and OprC_RND and one penAβ-lactamase, whose functions have been characterised were selected. The primer oligonucleotides for the genes BBSS1119 (MxFs_BPSS1119), bpeA (bpeA_RND), bpeB (bpeB_RND), amrB (MxYs_amrB), OprC_RND and penA were used to amplify the respective gene fragments. The majority of isolates were susceptible to imipenem, ceftazidime and co-amoxiclav, however there were few resistant strains to meropenem, cotrimoxazole, ceftazidime and co-amoxiclav among the animal and environmental isolates.Polymerase chain reaction (PCR) amplification of BPSS1119 RND, bpeA, bpeB andamrB gene fragment was obtained in all the 111 isolates of B. pseudomallei from animal or environment for all STs. However there was no amplification for B. pseudomallei RND efflux pump OprC and penAβ-lactamase gene fragments.Although this study detected the four RND efflux pump genes BPSS1119, bpeA, bpeB, amrB it is still not clear whether these efflux pumps have been expressed or not. The inability to detect OprC and penA gene could be attributed to gene deletion or due tothe occurrence of indels. We concluded that the efflux pump genes were widespread among animal and environmental B. pseudomallei regardless of isolate source and antibiotic resistance or susceptibility pattern.Physicochemical properties or characteristics of the environment where organisms dwell have been shown to influence the distribution of organism. A total of 78 isolates (56 from soil and 22 from water) from livestock farms environment were molecularly characterised by multilocus sequence typing (MLST) and were analysed against the environmental physicochemical properties from 33 livestock farms in four states of Pahang, Perak, Selangor and Negeri Sembilan in Peninsular Malaysia. Multinomial logistic regression performed found significant association between soil water content and ST84 (OR = 0.833, 95%CI 0.708 to 0.980; p=0.027) when compared to ST51. This shows unit increases in soil water content was associated with a 1.2 times increase in the odds of recovering ST51 compared with the odds of recovering ST84. Also statistically significant protective association was found between water pH and ST84 (OR=0.401 95%CI 0.195-0.828; p= 0.013) when compared to ST51. These findings suggest variation in the occurrence of various B. pseudomallei STs with the variations in the environmental (soil and water) physicochemical factors.In conclusion, this study recovered two novel alleles ace97 and lepA, and five novel STs, ST1130, ST1131, ST1338, ST1339 and ST1367.Burkholderia pseudomallei is highly clonal and is likely to have originated from the CC48 found regionally in Southeast Asia. The existence of few resistant strains to drugs that are essential in the treatment of melioidosis among animal and environmental isolates poses a clinically significant threat to the management of infected animals and human patients. An association was demonstrated between B. pseudomallei STs and resistance to meropenem among the animal isolates. Polymerase chain reaction (PCR) detection of the efflux pump genes showed widespread prevalence of these genes among animal and environmental B. pseudomallei regardless of antibiogram, source or genotype. Physicochemical properties such as soil water content and water pH play a role in influencing the distribution of genotype of B. pseudomallei in endemic areas. This information is useful for planning control programs tailored towards environmental interventions to reduce contamination in non-endemic areas.